Behavior-Based in Ground Handling Risk Management - Hoang Oanh, Le Thi (Digital Repository of Theses - SSBM Geneva, 2025)
Ground handling operations are vital to the aviation industry, ensuring safe and efficient aircraft turnaround. Despite technological advancements and the adoption of Safety Management Systems (SMS), ground handling remains a complex and challenging area, significantly influenced by human factors. This research explores persistent safety issues within ground handling, focusing on the behavioral risks that contribute to accidents and operational inefficiencies. Drawing from my extensive experience in the aviation sector, I have witnessed the difficulties of managing human behavior in high-pressure environments. This firsthand experience, combined with a professional commitment to advancing aviation safety, inspired the development of an Integrated Behavior-Based Risk Management Framework tailored to Vietnam's rapidly growing aviation industry. The study systematically examines behavioral risks in ground handling, utilizing data from employee surveys, interviews, and direct observations at multiple international airports across Vietnam. The findings highlight that both organizational and individual factors affect employee performance and safety outcomes. Key organizational challenges include resource limitations, communication gaps, and external factors like extreme weather. At the individual level, motivational deficiencies, skill deficits, and negative attitudes are major contributors to unsafe practices. In response, the proposed framework integrates behavior-based safety principles with traditional risk management practices, advocating for a holistic approach that combines technical controls with human behavior considerations. The framework includes interventions such as continuous employee training, improved communication channels, workload management, and cultivating a strong safety culture. It also emphasizes leadership's crucial role in shaping employee attitudes and ensuring compliance with safety protocols. While designed for Vietnam’s aviation sector, the framework is adaptable to other industries where human behavior critically impacts safety performance. This research advances the understanding of human factors in risk management within ground handling operations and offers practical recommendations. By addressing the interplay between organizational dynamics and individual behaviors, the framework provides a valuable tool for reducing accidents, improving operational efficiency, and enhancing safety performance. Its broader applicability positions it as a significant resource for global aviation safety practices. I am confident that this framework will play a pivotal role in shaping the future of aviation safety management, not only in Vietnam but also globally.